A new species of clausophyid calycophoran siphonophore (Cnidaria: Hydrozoa), Kephyes hiulcus sp. nov., widely distributed throughout the world's oceans - Grossmann, Mary Matilda; Lindsay, Dhugal John (Zootaxa, 2017)
A new species of clausophyid siphonophore, Kephyes hiulcus sp. nov. is described. It can most easily be differentiated from its congener Kephyes ovata by the shape of the hydroecium in the anterior nectophore of the polygastric stage. This is open over the entire height of the nectophore in K. hiulcus sp. nov., and it is this character from which its specific name is derived. This species was found in the eastern and western Pacific Ocean, as well as the Celebes and Mediterranean Seas, indicating that this species is both relatively common and geographically widespread.